(untitled) (Research, Society and Development, 2022)
Objective: to understand the impacts caused by the use of the internet in the midst of the COVID-19 pandemic. Methods: this is a systematic review of the literature with a qualitative approach and a descriptive-exploratory characteristic carried out in 2020. Results: there is a dichotomy related to the use of the internet in the midst of the pandemic of COVID-19. On the one hand, its use has triggered feelings of fear, anxiety, anguish, sadness, depression and even cyberchronicity, on the other hand, it has provided tranquility, mental well-being and has served as a psychological intervention strategy on online platforms. Final considerations: therefore, it is necessary to disseminate information to the population so that they can establish safe, moderate and equitable handling of this device, benefiting beneficially from the possibilities offered in order to make them an ally.